Russia in the Eyes of Islamic State: An Analysis of the Content of Dabiq and Rumiyah Magazines and Russia’s Involvement in the Fight against the Islamic State - Stempień, Marta Sara (Terrorism and political violence, 2021)
This paper analyzes a large content of the Islamic State (IS) English-language magazines Dabiq (fifteen issues, 2014–2016) and Rumiyah (13 issues, 2016–2017), which represent the largest text sample of IS propaganda prepared for English-speaking recipients. The author attempts to understand the propaganda methods and leading themes related to Russia exploited in the magazine. Research confirmed strong, omnipresent religious dualism between “believing” and “disbelieving” applied to non-religious entities, seen by Islamic State as enemies. Thus, military opponents, such as Russia are labeled with words such as Crusaders or unbelievers, while self-proclaimed caliphate is portrayed as the last Muslim bastion against the invaders. This article attempts to fill a gap in research on the Islamic State’s propaganda methods used in its flagship online magazines. Its major objective is to discover and understand the Islamic State’s approach to one of its biggest enemies—the Russian Federation. In order to reach this goal, quantitative and qualitative content analysis is used.